Trends in mortality after hospital admission for liver cirrhosis in an English population from 1968 to 1999. - Roberts, SE; Goldacre, M; Yeates, D (2005)
BACKGROUND: Population based mortality rates from liver cirrhosis, and alcohol consumption, have increased sharply in Britain in the past 35 years. Little is known about the long term trends over time in mortality rates after hospital admission for liver cirrhosis. AIMS: To analyse time trends in mortality in the year after admission for liver cirrhosis from 1968 to 1999. SUBJECTS: A total of 8192 people who were admitted to hospital in a defined population of Southern England. METHODS: Analysis of hospital discharge statistics linked to death certificate data. The main outcome measures were case fatality rates (CFRs) and standardised mortality ratios (SMRs). RESULTS: At 30 days after admission, CFR was 15.9% and the SMR was 93 (86 in men and 102 in women, compared with 1 in the general population). At one year, the overall CFR was 33.6% and SMR was 16.3. There was no improvement from 1968 to 1999 in mortality rates. SMRs were highest for alcoholic cirrhosis of the liver (27.4 at one year) but lower for biliary cirrhosis (11.4) and chronic hepatitis (10.0). Mortality from most of the main causes of death, including accidents and suicides, was increased. CONCLUSIONS: The high mortality rates after hospital admission, and the fact that they have not fallen in the past 30 years, show that liver cirrhosis remains a disease with a very poor prognosis. Increased mortality from accidents, suicides, and mental disorders, particularly among those with alcoholic cirrhoses, indicates that prognosis is influenced by behavioural as well as by physical pathology.